Opening the Great Depths The Bathyscaph Trieste and Pioneers of Undersea Exploration. - Polmar, Norman (Naval Institute Press, 2021)
Opening the Great Depths is the story of the Trieste, its officers and sailors, and the civilians, often told in their own words, documenting for the first time the earliest years of humanity's probing into Earth's final frontier.